(3GdehbYjI aj GdfMh GdYQHj (B:s (3OQGSI SjGbjI (B/s - (3MSjf, MSjf QaYJs; (3MSGf, JeGe,s 1918-2011 ((3GdbGgQI (B:s (3YGde GdcJH,s, 2010)
(3jJfGhd GdcJGH HGdOQGSI GdhGajI ehVhY GdehbYjI aj GdfMh hGdehbYjI aj GdfXGe GdUhJj hGdfXGe GdUQaj, ceG JfGhd GdcJGH ehVhY GdehbYjI aj VhA bQjfI GdJVGe, hCjVG GdehbYjI aj VhA bQjfI GdQHW eY YQV dHYV GdJQGcjH GddZhjI Ohf GdENdGd HbhGYO GdfMGI aj GdJQGcjH, eeG jOd Ydi Cf GdcJGH eQLY gGe dOGQSj GdbhGYO GdfMhjI hGdUQajI ef fGMjI OQGSI GdehbYjI(B. s
(3HHdjhLQGajI (B: (3UaMI (B337-345.s
Keywords: (3GddZI GdYQHjIs -- (3fMhs; (3GddZI GdYQHjIs -- (3EYQGHs